2017
DOI: 10.1007/s12603-016-0864-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of aerobic and resistance training combined with fortified milk on muscle mass, muscle strength, and physical performance in older adults: A randomized controlled trial

Abstract: These results suggest that AT before RT combined with fortified milk consumption has similar effects on skeletal muscle mass and strength compared with RT alone, but it may be a more useful strategy to improve physical performance in older adults. Although the mechanism of our intervention is uncertain, our program would be an effective prevention for sarcopenia in older adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 35 publications
1
28
0
Order By: Relevance
“…After the interven- tion, weight, body mass index, heart rate, brachial and ankle blood pressure, and ankle-brachial index were not significantly changed in each group. However, it was previously reported 13) that muscle strength and physical performance were significantly improved in both groups (data not shown). Fig.…”
Section: Resultsmentioning
confidence: 54%
See 3 more Smart Citations
“…After the interven- tion, weight, body mass index, heart rate, brachial and ankle blood pressure, and ankle-brachial index were not significantly changed in each group. However, it was previously reported 13) that muscle strength and physical performance were significantly improved in both groups (data not shown). Fig.…”
Section: Resultsmentioning
confidence: 54%
“…From the viewpoint of the promotion of muscle mass and strength, aerobic exercise before resistance training may be more effective because it is likely to stimulate muscle protein synthesis-dependent on vasodilation 18,19) . The beneficial effects of aerobic exercise before resistance training on muscle mass, muscle strength, and physical performance in older adults has been previously reported 13) . However, previous studies regarding vascular health have demonstrated that aerobic exercise after resistance training might have more effect on arterial stiffness 11,12) .…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Thus, plenty of evidence seek to bring strategies to minimize the effects associated with biological aging. 5,6 In an attempt to delay or mitigate these changes, physical training has been cited as a fundamental strategy to maintain functional capacity. 7 Aerobic training is an excellent strategy for the cardiovascular adaptations, since, over time, blood vessels lose elasticity, capillary diameter, and endothelial function, and also present a reduced blood capillaries/muscle fiber ratio.…”
Section: Introductionmentioning
confidence: 99%